Contribution of Islamic Law in Tackling Money Laundering Crimes in Indonesia - Muhammad Ridha Haykal Amal (International Journal Reglement & Society (IJRS), 2021)
Money laundering is an attempt by a person to hide the origin of the proceeds of the crime he has committed. When viewed from the origin of the word, money laundering comes from two syllables, namely washing and money. Washing means cleaning something dirty or attempts to remove dirt stuck to something, and money is a tool that is used to exchange something and is generally accepted. In Jinayah's point of view, money / property is obtained from a way that is vanity / haram, for example, obtained from taking / seizing property that is not his property, narcotics, terrorism and so on. On that basis, in order to eliminate traces of his / her crime, a person then laundered the "illegal money / property" in various ways including making his own business, investing, and so on, so that it is as if what is produced from his business or investment is a lawful result. . The sentence "laa ta'kuluu" in the above verse according to Indonesian tafsir expert Prof. Quraish Shihab does not only mean "to eat" in the sense of putting something in the mouth and swallowing it. However, the meaning also means "how to obtain or perform activities". The procedure used to collect data in this study is documentation, namely the guidelines used in the form of notes or quotations, search for legal literature, books and others related to the identification of problems in this study both offline and online. Analysis of legal materials is carried out using the content analysis method (centent analysis method) which is carried out by describing the material of legal events or legal products in detail in order to facilitate interpretation in the discussion. Explicitly, Islamic criminal law (jinayah) does not explicitly mention the term money laundering. He only mentions terms that have the same elements in his actions as money laundering, including theft, embezzlement, fraud, and treason.